Cooperative Learning for Improving Students' L2 Willingness to Write in Creative Writing - Hilarius Raditya Priambada Purba; Elsha Ridzky Fadila Darsono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The aim of this research is to investigate the effectiveness of cooperative learning in improving students’ L2 willingness to write in creative writing. To assess the effectiveness of the instrument in the study, classroom action research is the method that will be used to measure in student learning or achievement as a result of an intervention, a pre-test and post-test are commonly used instrument in classroom action research. The study’s finding revealed that the classroom action research group’s L2 willingness to write in creative writing improved significantly after the cycle of cooperative learning instruction. The findings support cooperative learning’s effectiveness in improving students’ L2 willingness to write in creative writing. According to the findings, incorporating cooperative learning into language instruction is a promising approach for improving writing skills in the L2 context. Keywords: Classroom Action Research, Cooperative Learning, Creative Writing, L2 Willingness to Write